Prevalence of Mitral Valve Prolapse and Its Adverse Sequelae in Healthy Adult Yemenis - Jayed, Dhaifullah; Aldholae, Mohamed Hider; Al–Huthi, Mohammed Ali (Thamar University Journal of Natural & Applied Sciences, 2023)
Background: Mitral valve prolapse is a common cardiac disease with frequent complications.Objectives: To study the prevalence of mitral valve prolapse in healthy Yemenis associated with the prevalence of its adverse sequelae.Methods: We performed echocardiography for 1164 healthy Yemeni individuals: 615 women and 549 men (mean age ± SD 45.7 ± 10 years).Classical mitral valve prolapse was defined as a superior displacement of mitral valve leaflets at least 2 mm with a maximal leaflets thickness of at least 5 mm during diastasis. On the other hand, nonclassic prolapse was defined as displacement of more than 2 mm with a maximal thickness of less than 5 mm.Results: 74 subjects (6.3 percent) had mitral valve prolapse, 40 (3.4 percent) had classic prolapse and 34 (2.9 percent) had nonclassic prolapse. None of the patients with prolapse had a history of heart failure nor anyone had atrial fibrillation except one patient (1.3 percent) had cerebrovascular disease and two patients (2.7 percent) had syncope, as compared with unadjusted prevalence of these findings on the individuals without prolapse of 0.0, 0.0, 0.0 and 1.3 percent, respectively. Chest pain, dyspnea and electrocardiographic change frequencies were similar between two groups.Conclusion: The prevalence of mitral valve prolapse in adult Yemenis was 6.3 percent, which is similar to the results of other studies in different countries but with low prevalence of adverse sequelae in comparison to those studies.